Into the blizzard : heroism at sea during the great blizzard of 1978 - Tougias, Mike, 1955- (True rescue series., 2019)
Young readers version of a story about a high-seas rescue operation involving the United States Coast Guard and a forty-nine-foot steel boat called the "Can Do," during a blizzard in 1978 off the Massachusetts coast. Describes the actions of Pilot boat Captain Frank Quirk and his crew of four who helped the Coast Guard assist a tanker in the midst of the storm.